Children's self-reported exposure to sugary beverage advertisements and association with intake across six countries before and during the COVID-19 pandemic: a repeat cross-sectional study - Élisabeth Demers-Potvin; Simone Lemieux; Rachel B. Acton; Tarra L. Penney; Gary Sacks; Christine M. White; Martin White; David Hammond; Lana Vanderlee (BMC, 2024)
Abstract Background Children's exposure to sugary beverage advertising may have changed during the COVID-19 pandemic due to shifts in media habits, which could subsequently have influenced intake. This study aimed to examine: 1) children's frequency and setting of exposure to advertisements of sugary beverages in six countries before and during the COVID-19 pandemic; 2) the association between exposure to sugary beverage advertisements and intake. Methods Children aged 10-17 years (n = 28,908) in Australia, Canada, Chile, Mexico, the United Kingdom (UK) and the United States (US) completed online surveys in 2019, 2020 and 2021 as part of the International Food Policy Study using a repeat cross-sectional study design. Respondents self-reported frequency and setting of exposure to sugary beverage advertisements, location of school classes (in-person/online, 2020-2021 only), screen time, and sugary beverage intake. Adjusted weighted logistic and negative binomial regression models stratified by country examined associations between year and reported sugary beverage advertising exposure, and associations between sugary beverage advertising exposure and intake. Differences in reported advertising exposure between students taking online or in-person school classes were explored. Results Self-reported exposure to advertisements for sugary beverages at least weekly was relatively stable across years within countries, with differences in settings of exposure. Exposure to sugary beverage advertisements increased on digital media independently of screen time from 2019 to 2021 in Australia, Canada, the UK and US, with a concomitant decrease in exposure in retail settings in all countries except the UK. In Australia and the UK, children attending all classes online were more likely to report at least weekly (vs less than once a week) exposure to sugary beverage advertisements, and children attending all classes online were more likely to report exposure to advertisements on digital media and in other settings (e.g., billboard, magazines) compared to children attending in-person classes in Australia, Canada and the UK. Exposure to sugary beverage advertisements at least weekly (IRR = 1.12,99%CI:1.09-1.15) and in each of the settings was associated with sugary beverage intake. Conclusions Exposure to digital advertisements for sugary beverages increased from 2019 to 2021 in most countries, and exposure was associated with sugary beverage intake. Reducing children's exposure to advertising of less healthy foods, including on digital media, may reduce sugary beverage intake.